Traffic identification of network business based on multi-layer cascade algorithm - Feng HUANG; Yao WANG; Li HUANG; Jiming YAO; Shidong LIU (Dianxin kexue)
The contradiction between traffic demand and network bandwidth is the main problem of the current network.Traffic management is one of the effective solutions,at the same time it can improve the quality of service of the network,and network traffic identification is the basis of fine traffic management.The traffic identification method of network business based on multi-layer cascade algorithm was proposed,after the research of network traffic identification and machine learning techniques.This method can adapt to the situation of the complex network traffic flow,and can balance the contradiction between the time performance and the accuracy of the machine learning algorithm.Furthermore the cascade algorithm of this method takes the cost imbalance into account,and takes more attention to the identification of important business,so it can help enhance user experience.